하수슬러지 유기성 고형연료의 점하중 시험에 의한 강도 예측 - 정일갑(Il-kab Jeong); 김태원(Tae-won Kim); 이동명(Dong-myung Lee); 강충길(Chung-gil Kang) (Daehan hwan'gyeong gonghag hoeji, 2018)
최근, 하수슬러지 유기성 고형연료에 대한 관심이 높아지면서 하수슬러지를 이용한 유기성 고형연료 생산방법 및 연료로서의 특성에 대한 연구가 이루어지고 있다. 하지만 연료화 된 하수슬러지 유기성 고형연료의 기계적 물성에 대한 연구는 진행되고 있지 않다. 본 연구에서는 암석의 점하중강도 시험을 통하여 하수슬러지 유기성 고형연료의 점하중 강도를 측정하고 이를 바탕으로 일축압축강도를 도출하여 하수슬러지 유기성 고형연료의 기계적 강도를 제시하고자 한다. 연구결과, 하수슬러지 유기성 고형연료의 보정된 점하중 강도(Is(50))은 최대 3.74 MPa, 최소 0.04 MPa이었다. 그리고, 점하중 강도를 통하여 추정된 하수슬러지 유기성 고형연료의 일축압축강도는 최대 89.78 MPa, 최소 1.08 MPa이었으며, 평균 24.86 MPa이었다. 하수슬러지 유기성 고형연료의 점하중강도 및 일축압축강도의 범위와 분포가 넓어 전체 값을 관찰하여 용도에 맞게 결과값을 활용해야 할 것으로 판단된다. Recently, interest has increased about sewage sludge solid refuse fuel. So, Studies have conducted on sewage sludge, the production method of solid fuel and the characteristics as fuel. However, studies on the mechanical properties of sewage sludge solid fuel have not been conducted. In this study, the point load strength of sewage sludge sloid fuel was measured by the point load strength test of rock and the uniaxial compressive strength was derived based on this. We propose the mechanical strength of sewage sludge solid fuel through the result of this study. As a result, the size corrected point load strength (IS(50)) of sewage sludge solide fuel was max. 3.74 MPa and min. 0.04 MPa. And, the uniaxial compressive strength of sewage sludge solid fuel estimated by the point load strength was max. 89.78 MPa, min. 1.08 MPa and the average was 24.86 MPa. The result of study should be observed all data and should be use according to the application. because the range and distribution of the point load strength and the uniaxial compressive strength of the sewage sludge solid fuel are wide. KCI Citation Count: 1